1992
DOI: 10.1002/j.1460-2075.1992.tb05572.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid activation of a novel plant defense gene is strictly dependent on the Arabidopsis RPM1 disease resistance locus.

Abstract: We cloned and sequenced cDNAs encoded by a novel plant defense gene, ELI3, from parsley and Arabidopsis thaliana. The predicted product shares no homology to known sequences. ELI3 mRNA accumulates in A. thaliana leaves in response to challenge with phytopathogenic Pseudomonas syringae strains. The timing and magnitude of this response are dictated by the genetics of the plant‐pathogen interaction being analyzed. During incompatible interactions, where resistance in the plant genotype Col‐0 is dictated by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 30 publications
2
81
2
Order By: Relevance
“…At least five Pseudomonas syringae avr genes are recognized by four unlinked Arabidopsis R genes (Dangl, 1993;Kunkel, 1995). The combinations analyzed in our experiments are avrRpt2-RPS2 (Whalen et al, 1991;lnnes et al, 1993;Kunkel et al, 1993;Yu et al, 1993) and avrRpm7-RPM1 (Debeneret al, 1991;Dangl et al, 1992;Ritter and Dangl, 1995). The respective avrgenes have never been observed to be present in the same bacterial strain.…”
Section: Introductionmentioning
confidence: 72%
“…At least five Pseudomonas syringae avr genes are recognized by four unlinked Arabidopsis R genes (Dangl, 1993;Kunkel, 1995). The combinations analyzed in our experiments are avrRpt2-RPS2 (Whalen et al, 1991;lnnes et al, 1993;Kunkel et al, 1993;Yu et al, 1993) and avrRpm7-RPM1 (Debeneret al, 1991;Dangl et al, 1992;Ritter and Dangl, 1995). The respective avrgenes have never been observed to be present in the same bacterial strain.…”
Section: Introductionmentioning
confidence: 72%
“…5). Two genes encoding components related to pathogen defense signaling ELI3-2 (At4g37990) and a WRKY family transcription factor, WRKY70 (At3g56400; Kiedrowski et al, 1992;Li et al, 2004), are misregulated in the hy5 mutant (Supplemental Table S6), suggesting that HY5 may be a key component of the cross talk between light and pathogen defense signaling. HY5 has been demonstrated to bind a G-box motif (Gao et al, 2004), and, consistent with this, bioinformatic analysis of our array data revealed that a classic G-box (CACGTG) or a G-box variant (CACGTH) were significantly enriched in the HY5 regulon versus the genomic average for these elements within Arabidopsis 500-bp promoter spaces (Table III).…”
Section: Discussionmentioning
confidence: 99%
“…Some paralogs (AtCAD-1, AtCAD-E, and -F) are close to MsaCAD1, a gene known to be wound inducible in alfalfa, where the corresponding protein is active on a range of cinnamyl, benzyl, and aliphatic aldehyde substrates (Brill et al, 1999). The AtCAD-B paralogs corresponding to ELI-3 proteins have been studied previously and were originally identified as part of the defense response in parsley (Petroselinum crispum) and in Arabidopsis (Kiedrowski et al, 1992). Williamson et al (1995) and Somssich et al (1996) demonstrated that ELI-3 was neither a CAD nor a malate dehydrogenase but rather a benzyl alcohol dehydrogenase, which accepts various benzaldehyde substrates.…”
Section: Atcad-c and Atcad-d Belong To A Small Multigene Family In Armentioning
confidence: 99%